TEACHING ENGLISH FOR NURSING BY USING TASK-BASED LANGUAGE TEACHING - Kailani, Ahmad; Murtiningsih, Tenny (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2019)
English for nursing is one of the branches of English for Specific Purposes. This type of English lesson requires the teacher to choose a specific method in order to meet a specific learning objective. The final goal of learning this kind of English is to equip learners with competencies that suit their future job, one of them, is English skill. This is inseparable from the choice of an appropriate teaching method by the teacher. Many studies on the implementation of specific teaching methods have been undertaken. However, little is still known about the students' responses to the implementation of Task-Based Language Instruction in English for Nursing Classes. To fill this gap, the current study shed a light on this matter. This qualitative research aimed to explore students’ perception of this teaching method. There were 58 nursing students invited as the respondents. The data were garnered through interview and questionnaires. The implication of this research is to be contributed to the field of EFL teaching methodology as the expansion for the current studies in English for specific Purposes field.